The law against war : the prohibition on the use of force in contemporary international law - Corten, Olivier (London, England : Zed Books, 2021)
"When this first English language edition of The Law Against War published it quickly established itself as a classic. Detailed, analytically rigorous and comprehensive, it provided an indispensable guide to the legal framework regulating the use of force. Now a decade on the much anticipated new edition brings the work up to date. It looks at new precedents arising from the Arab Spring; the struggle against the "Islamic State" in Iraq and Syria; and the conflicts in Ukraine and Yemen. It also reflects the new doctrinal debates surrounding recent state practice. Previous positions are reconsidered and in some cases revised, notably the question of consensual intervention and the very definition of force, particularly, to accommodate targeted extrajudicial executions and cyber-operations. Finally, the new edition provides detailed coverage of the concept of self-defense, reflecting recent interpretations of the International Court of Justice and the ongoing controversies surrounding its definition and interpretation"--
A choice of method -- What do 'Use of Force' and 'Threat of Force' mean? -- Do the prohibition of the use of force and self-defence apply to non-state actors? -- Can circumstances precluding wrongfulness be invoked to justify a use of force? -- Intervention by invitation -- Intervention authorised by the UN Security Council -- Self-defence -- A right of humanitarian intervention?
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: War (International law); Public international law; Electronic books